Genomic characterization and prognostic significance of copy number alterations in Tunisian patients with acute lymphoblastic leukemia - Ameni Bedoui; Wajdi Ayadi; Nour Louati; Imen Frikha; Yosra Fakhfakh; Fahmi Smaoui; Ali Gargouri; Ikram Ben Amor; Moez Elloumi; Moez Mdhaffar; Raja Mokdad Gargouri (PLoS ONE, 2026)
Acute lymphoblastic leukemia (ALL) is a heterogeneous malignancy characterized by various genomic alterations playing a crucial role in disease classification, prognosis, and response to treatment. However, molecular diagnosis and effective management of this hematological malignancy remain a major challenge, particularly in developing countries, including Tunisia. In this study, we aimed to conduct a detailed analysis of copy number alterations (CNAs) associated with ALL in a cohort of 60 primary samples from Tunisian patients. Using multiplex ligation-dependent probe amplification (MLPA), major genetic lesions, including IKZF1 , CDKN2A/2B , PAX5 , ETV6 , BTG1, and genes located in the PAR1 region, were analyzed and their associations with clinical and laboratory features, as well as survival outcomes, were also evaluated. Our analysis revealed that 70% of patients had deletions and/or amplifications in at least one gene. The most frequently observed deletions were in CDKN2A/2B (33.3%, n = 20), IKZF1 (30%, n = 18), and PAX5 genes (25%, n = 15). BTG1 deletions were significantly associated with female gender, IKZF1 deletions were more frequent in adult patients, in those with elevated white blood cell (WBC) counts, and in cases involving the BCR::ABL1 translocation, while duplications of the PAR1 region were significantly associated with hyperdiploïdy. Regarding treatment response, cases of IKZF1 deletions showed a significant association with poor glucocorticoid response (GC) at day 8 of treatment and positive minimal residual disease (MRD) rates at days 33 and 63, particularly in B-ALL cases. Furthermore, patients with IKZF1 deletions were associated with significantly lower survival rates in both univariate and multivariate analyses compared to those without these deletions. Additionally, the integration of IKZF1 deletion status into risk stratification models revealed markedly different survival outcomes, highlighting its potential interest in developing new stratification algorithms. These results underscore the critical importance of molecular profiling, particularly IKZF1 status, for improving outcomes in ALL patients in Tunisia.